N2AFRICA farmer beneficiary_IITA Rwanda - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
IITA Rwanda implemented N2Africa project from 2010-2017. The project aimed at enabling smallholder farmers to benefit from nitrogen fixation by legume crops in Rwanda. This short video explains some of the commendable outcomes of project, such as new varieties of soybeans introduced and are very productive and novel technique of intercropping maize and soybeans.